Perlindungan Hukum Bagi Debitur Terhadap Kreditur Pada Perjanjian Kredit Di Koperasi Simpan Pinjam - Sapardi, Gabriela; Haliwela, Nancy Silvana; Pariela, Marselo Valentino Geovani (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
Law Number 17 of 2012 regulates cooperatives, one form of which is savings and loan cooperatives which aims to improve the welfare of members in particular and society in general, as well as being an inseparable part of a democratic and just national economic order, but in reality cooperatives savings and loans are very difficult for members or the community as debtors because the agreement is only made unilaterally, namely from the cooperative and there is no clarity regarding fines and interest if the debtor is late in paying, this makes the debtor feel very disadvantaged. This research method is a normative method that is descriptive. Which consists of research types, the problem approach used is a statutory approach and a conceptual approach, legal materials consisting of primary legal materials, secondary legal materials and tertiary legal materials, procedures for collecting legal materials, and finally processing and analysis of legal materials. The research results show that the implementation of credit in savings and loan cooperatives begins with entering into a credit agreement, the parties have rights and obligations that must be fulfilled. Debtors are obliged to pay installments, fines and interest, while creditors have an obligation to pay installments, provide explanations and understanding to debtors about the contents of the agreement, payment of installments, fines and interest. Legal protection for debtors in credit agreements, namely preventive legal protection and repressive legal protection. Preventive Legal Protection means that the debtor receives clear information regarding the rights and obligations contained in the contents of the credit agreement between the debtor and the cooperative, while Repressive Legal Protection is an effort to resolve problems when a dispute occurs. In this case, the debtor can submit complaints and complaints to the Financial Services Authority (OJK) if they feel disadvantaged. Therefore, cooperatives must be more selective in providing loans to debtors, so that the loans provided do not have problems because this can disrupt the cooperative's finances. And the cooperative must supervise the debtor in using the loan so that the loan can be returned to the cooperative in accordance with the agreement. The government, in this case, the OJK, must increase supervision of savings and loan cooperatives, the OJK must supervise the regulations made by the cooperative. The community must increase financial literacy by providing gradual socialization about the benefits and risks of using cooperatives.